LOYALITAS KAUM SUFI TERHADAP SYARIAT - Dimyati Sajari (Universitas Islam Negeri Jakarta, 2014)
Loyalty Sufis against Shari’ah. In the history of Islam, the Sufis always received criticism from some scholars that they ignore the laws of Sharia. Sufis are considered more priority the inner problem than Shari’a law. This paper proves that the criticism is not always true. The majority of the Sufis still loyal and running the Shari’a law. Even many Sufis who follow the habit of the Prophet until the small things that are not considered essential. Although a small group of Sufis who ignore the law, who are a small part of the malâmatiyyah, but this can not be generalized for all Sufis.DOI: 10.15408/ajis.v14i1.1249